2016
DOI: 10.1007/s10569-016-9697-9
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and numerical manifolds in a symplectic 4-D map

Abstract: We study analytically the orbits along the asymptotic manifolds from a complex unstable periodic orbit in a symplectic 4-D Froeschlé map. The orbits are given as convergent series. We compare the analytic results by truncating the series at various orders with the corresponding numerical results and we find agreement along a more extended length, as the order of truncation increases. The agreement is improved when the parameters approach those of the stability domain. Along the manifolds no terms with small di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…The validity of our findings was checked again by finding parameter values at which homoclinic orbits disappear through a tangency of the corresponding manifolds. What is remarkable, both in the 2D and in the 4D case it was possible to accurately locate homoclinic points just using the parametrization method without any additional application of the mapping or its inverse (see [34,37] for another approach).…”
Section: Discussionmentioning
confidence: 99%
“…The validity of our findings was checked again by finding parameter values at which homoclinic orbits disappear through a tangency of the corresponding manifolds. What is remarkable, both in the 2D and in the 4D case it was possible to accurately locate homoclinic points just using the parametrization method without any additional application of the mapping or its inverse (see [34,37] for another approach).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of the plateaus can be explained by the alternating spiraling in and out of the dynamics already observed in Refs. [6,11,36,38]: An orbit initially started near the complex unstable fixed point moves away from it on a spiral along the unstable manifold until it reaches a maximal distance to the fixed point. This behavior corresponds to the first expansion phase up to approximately 100 iterations.…”
Section: Escape Statisticsmentioning
confidence: 99%
“…A distinctive feature is the spiraling motion in the surrounding of a complex unstable periodic point [6,30]. Moreover, it was found that commonly an extended region around a complex unstable fixed point emerges to which the dynamics is confined for rather long times [11,[36][37][38]. Important approaches to understand the complex unstable dynamics are based on computations of the invariant manifolds [36,38,39] and normal form descriptions [15,40,41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In galactic dynamics it characterizes periodic orbits of many three dimensional (hereafter 3D) models in a large volume of their parameter space (Magnenat, 1982a,b;Pfenniger, 1984Pfenniger, , 1985bContopoulos and Magnenat, 1985;Contopoulos, 1986;Martinet and Pfenniger, 1987;Pfenniger, 1987;Martinet and de Zeeuw, 1988;Zachilas, 1988;Patsis and Zachilas, 1990;Zachilas, 1993;Patsis and Zachilas, 1994;Olle and Pfenniger, 1998;Katsanikas, Patsis and Contopoulos, 2011;Patsis and Katsanikas, 2014). However, considerable insight in the role of complex instability for the dynamics of Hamiltonian systems has been gained by works on several other kinds of potentials (Heggie, 1985;Papadaki, Contopoulos and Polymilis, 1995;Ollé and Pacha, 1999) or 4-dimensional symplectic mappings (Pfenniger, 1985a;Contopoulos and Giorgilli, 1988;Olle and Pfenniger, 1995;Jorba and Ollé, 2004;Delis and Contopoulos, 2016;Stöber and Bäcker, 2021). These results have also been used for understanding the behaviour of stellar orbits in galactic type potentials.…”
Section: Introductionmentioning
confidence: 99%